THE INTEREST OF THE YOUNGER GENERATION IN GROUPER FARMING IN LEMBUNG VILLAGE, GALIS DISTRICT, PAMEKASAN REGENCY - Putri Dwi Nurlaily; Slamet Widodo; Amanatuz Zuhriyah; Jeter Donald Siwalette (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
The aging farmer and aging fisherman is a challenge in Indonesia's agriculture and fisheries sector. Without regeneration, the economy, employment, and food security will be threatened. One of the fisheries sectors with good prospects is aquaculture, such as grouper farming in Pamekasan Regency. This research aims to assess the level of interest among the youth and identify factors that influence their interest in grouper farming in Lembung Village, Galis Sub-district, Pamekasan Regency. The respondents in this research were 30 youth aged 16-30 years who were determined purposefully. Primary data was collected by interview and observation and analyzed by descriptive quantitative and multiple linear regression. The results showed that the level of interest of the youth in cantang grouper aquaculture in Lembung Village, Galis Sub-district, Pamekasan Regency was in the medium category. This interest is influenced by motivational factors. It requires steps to continuously increase the interest of the youth in cantang grouper aquaculture through government and community cooperation. Government support can be in the form of training, counseling, and capital access assistance. In addition, strengthening groups of cultivators to guide and share experiences with the youth is highly necessary.